HOW TAX POLICIES SHAPE INVESTMENT DECISIONS IN EMERGING ECONOMIES - DOBROTĂ GABRIELA; DAN NICOLETA; POPA DANIELA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
This research examines the impact of fiscal policy on private investment in emerging economies, focusing on the effects of indirect taxes, public expenditures, and budget deficits. The methodology includes econometric analyses, using a multiple regression model to assess the relationship between direct taxes, government spending and the budget deficit, relative to private investment. The findings confirm the hypothesized relationships: indirect taxes negatively affect private investment, infrastructure-focused public spending stimulates investment, and large budget deficits create uncertainty that discourages investment. These results underscore the importance of a balanced and strategic fiscal policy approach in emerging economies. Policymakers should consider reducing reliance on indirect taxes, prioritizing public spending on infrastructure development, and maintaining fiscal discipline to foster a favorable environment for private investment and sustainable economic growth.